2021
DOI: 10.1093/geront/gnaa219
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Elevated Inflammation Among Chinese Older Adults: Eight Years After the 2003 SARS Epidemic

Abstract: Background and Objectives This study examined associations between exposure to the 2003 Severe Acute Respiratory Syndrome (SARS) epidemic and Chinese older adults’ depression and inflammation 8 years after the crisis. Further, this study investigated the buffering effects of perceived social support and social participation. Research Design and Methods Data were drawn from the 2011 China Health and Retirement Longitudinal Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…The lung and immune system are the main target organs of SARS and COVID-19, manifesting focal and patchy necrosis of lymph nodes and spleens, together with remarkable decreases in lymphocyte counts (81)(82)(83). COVID-19 has this kind of performance, but it is not as obvious as SARS.…”
Section: Crp and Other Viral Infections Crp And Sarsmentioning
confidence: 99%
“…The lung and immune system are the main target organs of SARS and COVID-19, manifesting focal and patchy necrosis of lymph nodes and spleens, together with remarkable decreases in lymphocyte counts (81)(82)(83). COVID-19 has this kind of performance, but it is not as obvious as SARS.…”
Section: Crp and Other Viral Infections Crp And Sarsmentioning
confidence: 99%
“…The vast majority of residents have cognitive disorders ( Helvik et al, 2015 , Nuutinen et al, 2020 ) which are likely to affect their ability to comprehend the pandemic and the visiting restrictions. It is known that social isolation increases morbidity and mortality ( Holt-Lunstad, 2018 ) and, as one might assume, the first studies on the lockdown have reported negative impacts on the well-being of older adults (e.g., ( Macdonald and Hülür, 2021 , Kim and Jung, 2021 , Wang et al, 2021 )). Brooks et al ( Brooks et al, 2020 ) identified post-traumatic stress symptoms, confusion, and anger in residents, whereas Lima et al ( Lima et al, 2020 ) found that separation from loved ones led to despair among residents, and the feeling that the world was ending.…”
Section: Introductionmentioning
confidence: 99%
“…Lett., 2021, 8(4): [20][21][22][23][24][25][26] care services in the community and due to an increase in their population, demand for their services is increasingly growing. Their treatment differs from other age groups so that the cost of treatment in the elderly is twice that of a young person [4]. Depression is more common in the elderly than the general population, and various studies have reported the prevalence of depression in the elderly at 25 to 50 percent.…”
Section: Pourshams and Shhrooiementioning
confidence: 99%